THE EFFECT OF AUDIT CAPACITY STRESS AND AUDITOR EXPERIENCE ON AUDIT QUALITY WITH AUDITOR COMPETENCE AS A MEDIATION VARIABLE - Acila, Trista; Dahlan, Ahmad; Hastuti, Sri; Endah Aprillia, Mitha (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Audit quality is the ability of an auditor to find and report discrepancies in a client's accounting system using a structured system. This study aims to empirically analyze the effect of audit capacity stress and auditor experience on audit quality with auditor competence as a mediating variable on employees of Public Accounting Firms in Malang City. This study uses quantitative research methods. Respondents in this study were employees who worked as senior auditors. The population in this study was 18 KAPs in Malang City. The sample in this study used purposive sampling so that the number of samples that could be processed was 57 samples. The analysis tool used SEM-SmartPLS. The results of the study indicate that audit capacity stress does not significantly affect audit quality. Auditor experience significantly affects quality. Audit capacity stress significantly affects auditor competence. Auditor experience significantly affects auditor competence. Auditor competence significantly affects audit quality. Auditor competence is unable to mediate the effect of audit capacity stress on audit quality. Auditor competence is able to mediate the effect of auditor experience on audit quality